LEGALIZE CUSTOM-RELATED LANDOWNERSHIP TRANSACTIONS: THE INDONESIAN EXPERIENCE - Abdul Wahid; Siti Malikhatun Badriyah; Ahmad Muhamad Mustain Nasoha; Zamzami Zamzami (Diponegoro Law Review, 2023)
The secret sale of land raises changes in certificate ownership dilemma. The absence of seller during creation of the Deed of Sale and Purchase (AJB) poses a severe obstacle, coupled with the buyer's lack of knowledge. Another constraint is buyer's inability to create a deed due to seller's unknown address. This research highlights buyer's efforts to overcome obstacles in transferring land certificates from off-the-record land transactions. This is a normative legal approach through literature analysis. The results show that buyers can overcome obstacles by filing a lawsuit for unlawful actions in the district court where the land is located. This lawsuit is related to unlawful actions by the defendant, such as rejection or hindrance to changing the land certificate's name. Through the trial, the court can issue an order instructing the National Land Agency (Badan Pertanahan Nasional or BPN) to transfer the land certificate in the buyer's name. Even without the Deed of Sale and Purchase (AJB), the court order serves as a legal basis for BPN to execute this process. Upon completion, the buyer obtains legal certainty regarding land ownership, and despite lacking AJB, the renamed land certificate becomes valid proof of the buyer's land ownership.